The Irish matchmaker : a novel [large type] - Deibel, Jennifer, 1978- (Thorndike Press large print Christian romance series., 2024)
"As daughter of a well-known matchmaker, Catríona Daly is no stranger to the business of love--and sees it as her ticket away from the sleepy village that only comes alive during the annual matchmaking festival. Enter Lord Osborne's son, Andrew, who has returned to the festival after being disappointed by a rival matchmaker's failed setup. Catríona seizes the opportunity to make a better match for the handsome man--and for herself! Cattle farmer Donal Bunratty is in desperate need of a wife after loss left him to handle the farm and raise his daughter on his own. Shy and lacking the finer social graces, he agrees to attend the matchmaking festival to appease his daughter. But when he arrives, it's not any of the other merrymakers that catch his eye but rather his matchmaker--who clearly has eyes for someone else. Catríona will have to put all her expertise to work to make a match that could change her life forever. Will her plan succeed? Or will love have its own way? "--